PERLINDUNGAN HUKUM DAN KEPASTIAN HUKUM KEPEMILIKAN TANAH MELALUI PENDAFTARAN TANAH BERDASARKAN SISTEM PUBLIKASI NEGATIF BERTENDENSI POSITIF - Gunawan Gunawan; Happy Yulia Anggraeni; Ligar Ayu Pramesty (LPPM Universitas Ekasakti Padang, 2023)
Indonesia as a state based on law has regulated public welfare, especially regarding ownership of land rights guaranteed in the Basic Agrarian Law Number 5 of 1960 (UUPA). However, in practice regarding land registration there are still various problems. Because certificates, which are the end product of land registration, can still be canceled as a result of the publication system adopted. The purpose of this study is to understand the extent of legal protection and legal certainty of ownership of land rights through a positive negative publication system. The research method is Normative, a scientific research approach to find the truth based on the logic of legal science from the normative side. Based on the results of this study it can be concluded that the ownership of land rights through land registration with a negative publication system with a positive dimension is appropriate but in its an implementation it does not guarantee legal certainty for certificate holders because certificates are strong evidence so that they can still be sued within a period of 5 years. Arrangements regarding the time period for a lawsuit to cancel a certificate need to be amended, because since the certificate is issued 5 years is enough time for the certificate holder to face the possibility of a lawsuit.